TEACHER’S SCAFFOLDING TO PROMOTE TEACHING TRANSACTIONAL AND INTERPERSONAL CONVERSATION - YULI YULIANTI (Journal of English Education Program (JEEP), 2019)
This paper reports the effectiveness of teacher’s scaffolding to promote teaching transactional and interpersonal conversation. This study was aimed at finding out the kinds of scaffolding which are used by the teacher in teaching transactional and interpersonal conversation and the teacher’s reasons of using scaffolding to promote teaching transactional and interpersonal conversation. The study employed a qualitative research design, the writer used a case study as the way to figure out teacher’s scaffolding to promote teaching transactional and interpersonal conversation. The instruments used in this study consisted of two instruments including observation and interview. The findings revealed that the teacher used offering explanations, inviting students’ participation, verifying and clarified student understandings, and modelling to promote students’ conversation. Based on these findings, scaffolding is one of teaching process in order to make students enjoy the teaching and learning. It is aimed at helping students to accomplish their task through scaffold them with various ways. In conclusion, teacher’s scaffolding was helpful and effective to promote teaching transactional and interpersonal conversation.